Experimental Study on the Discharge Characteristics of a Dripping ‘Rod–Plane’ Air Gap at High Altitude Under DC Voltages - Chuyan Zhang; Xi Wang; Xinzhe Yu; Kaixuan Qu; Yuxi Dong; Yu Deng (Energies)
High-voltage transmission and substation projects at high altitudes are pivotal in realizing the objective of universal electricity access. However, the reduced air density at elevated heights facilitates the formation and propagation of discharges, posing more stringent challenges to the external insulation of these projects compared to their counterparts in plains areas. Furthermore, considering the influence of meteorological conditions such as rainfall, it is imperative to conduct comprehensive experimental studies on the insulation properties of air gaps to inform the design and maintenance of engineered external insulation. This paper presents the results of rod–plane gap discharge tests conducted under dripping conditions at an actual high-altitude location of 2500 m. The employed test methodology effectively simulates the impact of rainfall on the insulation characteristics of the gap. Based on the experimental findings, a detailed analysis is conducted on the effects of gap distance, dripping flow rate, and conductivity on the gap breakdown voltage. Additionally, the discharge paths and underlying mechanisms under water-dripping conditions on rod electrodes are briefly discussed. The acquired data and conclusions contribute to a deeper understanding of the mechanisms governing rainfall effects on gap discharges and provide valuable insights for the design of external insulation in high-altitude HVDC transmission projects.